Conserved elements within open reading frames of mammalian Hox genes - Woltering, Joost M (BioMed Central, 2009)
A recent study in BMC Evolutionary Biology shows that many of the open reading frames in mammalian Hox genes are more conserved than expected on the basis of their protein sequence. The presence of highly conserved DNA elements is thus not confined to the noncoding DNA in neighboring regions but clearly overlaps with coding sequences. These findings support an emerging view that gene regulatory and coding sequences are likely to be more intermingled than once believed.